Rhine low water crisis: From individual adaptation possibilities to strategical pathways - Gobert, Julie; Rudolf, Florence (Frontiers in Climate, 2023)
In 2018, the Rhine transport sector experienced an unprecedented low water crisis, during which large cargo vessels were no longer able to navigate on certain sections of the river. This led to a major disruption in inland waterway transport. This article aims at questioning how the crisis acts as a stimulus for port authorities and their customers to consider the risks for their assets and operations and as a window of opportunity for creating new collectives and for defining “solutions.” Climate change adaptation can offer the opportunity to question existing communities, which until now had assured daily procedures and mutual confidence or indifference. Inspired by the Impact Chain methodology, a step-by-step protocol was applied so that stakeholders affected by low waters can identify their individual and common vulnerability and define possible ways of acting. The combined methodology, integrating focus groups and interviews, allowed for the determination of individual and collective adaptation pathways. The transitional infrastructural strategy appears as the most suitable because it is a technical, well-controlled process that provides a comfortable solution in the short term. It exemplifies the lock-ins set by infrastructure. However, the participative approach also highlights the fundamental challenge of developing new processes and new intermodal organisations.